The Effect Of Potassium Permanganate On Betung Bamboo (Dendrocalamus Asper) Epoxy Fiber Compositesusing Hand Lay Up Method - Andriyansah; Zaid Sulaiman; Lucas Cramer (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2022)
The application of natural fiber composites in the modern world is often overlooked due to the rise of new synthetic fibers. The BetungBamboo is one type of natural fiber that has been used for many generations in the Indonesian archipelago. The fiber can be used to produce composites, however the choice of matrix and fiber treatment has an effect on determining the strength properties of the composite. In this study using epoxy resin as a matrix and Betung Bamboo fiber as a filler. Permanganate treatment of Betung bamboo fiber was conducted using KMnO4 solution. With variations in KMnO4 concentrations of 3%, 5%, and 7% for 15 minutes of immersion. The fabrication was carried out by hand lay-up method with silicone rubber molds. Tensile tests are then carried out to determine the tensile strength of the composite. Digital microscopy was observed to see the fracture pattern of the composite. The initial hypothesis of this study was the treatment of KMnO4 solution which aims to improve the interfacial properties of strength and resistance of Betung bamboo fiber and matrix, so that the mechanical properties of the composite are stronger. The highest tensile strength was at 5% KMnO4 content of 33.55 MPa and the lowest was at the specimen without KMnO4 content of 28.06 MPa. The highest strain was on specimens without KMnO4 content with 2.645% and the lowest on 7% KMnO4 content with 1.513%. The highest elastic modulus value was at 7% KMnO4 content of 20.84 MPa and the lowest was for specimens without KMnO4 content of 10.6 MPa. In the tensile test specimen without KMnO4 content, there are pullout fracture patterns, and in the tensile test specimen with 5% KMnO4 content there are indications of overload fracture pattern.